Risk identification from maternal and neonatal data for improvements in Quality of Care: A comparison of audit based approach with Maternal and Child Tracking System and Verbal Autopsy - Kumar HN, Harsha; Baliga, Shantaram B; Kushtagi, Pralhad; Kamath, Nutan; Rao, Sucheta S (National Journal of Community Medicine, 2021)
Background: Maternal and Child Tracking System (MCTS) and Verbal Autopsy (VA) are inadequate in risk identification from the available maternal and neonatal data. Hence community-based audit approach is required. Maternal and neonatal data obtained from MCTS, VA were compared with data obtained from the Audit model to know the differences in: (1) Quantity of information. (2) Relevance of the information. Methods: Perinatal death auditing was conducted in two districts of Karnataka state with the help of an expert panel consisting of paediatricians and obstetricians. Information on perinatal deaths were received from hospitals as well as from the community. Data collection tool covered details pertaining to care received, transport, referral, apart from socio-demographic details. Medical Social Workers collected filled tools from the hospitals. Maternal and neonatal data of audit model was compared with that obtained from MCTS and VA. Results: The data captured from audit model (n=1032) was more than MCTS (n=224) and VA (n=165) as it included the data from private hospitals and community. Maternal and neonatal risk identification was possible with audit system but not with MCTS and VA. Conclusion: Audit system is comprehensive and provides inputs for health care planning.